Pengetahuan ibu dan praktik pemberian MPASI pada anak stunting usia 6-24 bulan di Kabupaten Natuna: Studi Kualitatif - Misna Hidayati; Effatul Afifah; Arif Sabta Aji; Hastrin Hositanisita; AD Nabiella; Hammada Hanifia Mumtaz; Safira Nurlita (Jurnal SAGO Gizi dan Kesehatan, 2026)
Background: Stunting, a chronic condition resulting from prolonged malnutrition, is influenced by maternal education, knowledge, and attitudes. The lack of knowledge regarding complementary feeding can influence maternal attitudes. Natuna Regency is a 3 area (frontier, outermost, disadvantaged) region; therefore, there has been limited study on complementary feeding in this region. Stunting in children can adversely affect brain development, motor skills, and overall physical growth.Objective: To explore maternal knowledge and practices related to complementary feeding (CF) among mothers of stunted and non-stunted children aged 6–24 months in the Natuna Regency.Methods: This qualitative study used a descriptive-analytic design in Serasan and Serasan Timur Health Centers. from September to October 2024. Informants included 18 mothers (FGDs) and four key informants, two heads of health centers, and two nutritionists (in-depth interviews). Thematic analysis focused on timing, early initiation, feeding frequency, and CF schedules using NVivo 12.0.Results: Mothers of non-stunted children were more knowledgeable and adaptive in complementary feeding (CF) practices, whereas mothers of stunted children tended to rely on food availability and non-nutritional strategies. Both groups preferred homemade CF foods because of economic, health, and variety considerations. These qualitative findings are consistent with the quantitative results, which demonstrated a significant association between CF practices and stunting incidence (p < 0.001).Conclusion: Mothers of non-stunted children demonstrated more effective and responsive feeding practices. These findings highlight the importance of maternal knowledge and creativity in supporting optimal child nutrition and reducing stunting prevalence.